Effectiveness and safety of eleven Chinese patent medicines combined with atorvastatin in the treatment of hyperlipidemia: a network meta-analysis of randomized controlled trials - Shi, Zeyang; Zheng, Wei; Bu, Zhijun; Zhou, Xian; Wang, Xuefeng; Song, Yike; Sun, Jialin; Liu, Jian-Ping; Liu, Zhao-lan (Frontiers in Endocrinology, 2025)
BackgroundRandomized controlled trials (RCTs) suggested that combining Chinese patent medicines with atorvastatin exhibited superior effectiveness in treating hyperlipidemia with reduced adverse reactions. However, the evidence regarding the clinical effectiveness and safety was not assessed to make informed decision in clinical practice.ObjectiveTo evaluate the clinical effectiveness and safety of combined Chinese patent medicines with atorvastatin.MethodsEight databases (CNKI, Wanfang, VIP, SinoMed, PubMed, Embase, Web of Science, and Cochrane Library) were searched from inception to April 2024. The risk of bias (ROB) of the included RCTs was assessed using the ROB 2.0 tool recommended by the Cochrane Handbook. The surface under the cumulative ranking curve (SUCRA) probability values were used to rank the treatment measures, and the Confidence in Network Meta-Analysis (CINeMA) software was used to assess the grading of evidence.ResultsA total of 23 RCTs involving 2184 patients with hyperlipidemia were included. Hedan (tablets or capsules) combined with atorvastatin showed the highest clinical effectiveness with an RR of 1.58 (95% CI: [1.14, 2.12]) (SUCRA: 80.36%), the lowest post-treatment low-density lipoprotein cholesterol (LDL-C) level with an MD of -8.13(95% CI: [-9.70, -6.57]) (SUCRA: 3.37%), and the lowest post-treatment triglyceride (TG) level with an MD of -6.43(95% CI: [-7.71, -5.16]) (SUCRA: 0.33%). Dantian Jiangzhi Granules demonstrated the lowest post-treatment total cholesterol (TC) level with an MD of -2.22(95% CI: [-2.60, -1.83]) (SUCRA: 12.6%), while Xuezhikang Capsules displayed the highest post-treatment high-density lipoprotein cholesterol (HDL-C) level with an MD of 1.61(95% CI: [0.82, 2.39]) (SUCRA: 79.87%). However, it is important to note that most of the included studies showed “some concerns” regarding the risk of bias based on ROB 2.0. According to CINeMA, most confidence rating results were classified as “low”.ConclusionCompared to atorvastatin alone, the combination of Chinese patent medicines with atorvastatin demonstrated superior effectiveness in treating hyperlipidemia. Among these, Hedan (tablets or capsules) exhibited the greatest overall benefit, significantly reducing TG and LDL-C levels. Dantian Jiangzhi Granules had the most pronounced effect in lowering TC, while Xuezhikang was most effective in improving HDL-C level. Although Xuezhikang is well-documented as lipid-lowering agent, the findings of this study suggest that hyperlipidemia treatment should be tailored to individual blood lipid profiles. Additionally, for drugs with limited evidence of efficacy and safety, larger randomized controlled trials and further pharmacological studies are necessary to valid these results.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024573421.